CLINICAL AND MORPHOLOGICAL CHARACTERISTICS KERATOCYST OF THE JAWS IN CHILDREN - Tkachenko, P.I.; Starchenko, I.I.; Bilokon, S.O.; Lohmatova, N.M.; Sheshukova, Ya.P. (World of Medicine and Biology, 2012)
The article presents the clinical and morphological characteristics of keratocyst in children who make up only 5.05% of the planned surgery because of cystic formations jaw bones, which causes some difficulty in determining the first clinical manifestation of the disease and early detection of pre-hospital. Special attention is paid to decide the fate of the permanent teeth and determining the extent of surgical intervention, which may affect the appearance of the teeth-jaw deformities in the late periods. Verification of the morphological structure of cystic formation, to some extent, can be defined in the tactical approach to comprehensive dental support these patients in the postoperative period and setting the time and the amount of its holding.
Keywords: children; keratocyst